2014
DOI: 10.1007/s00383-014-3653-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pediatric intussusception complicated by loss of intestine viability in China from June 2009 to May 2014: a retrospective study

Abstract: The result of our risk factor analysis for loss of intestine viability in pediatric intussusception cases may help develop a predictability index to prevent the complication to happen. Further prospective studies are required to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…In our study, none of the 11 patients who underwent surgical reduction required resection due to bowel ischemia. Xian-Ming et al concluded that the median time between symptom onset and operative treatment for intussusception was longer in patients who lost intestinal viability (42 h) than for those who did not (19 h) [17]. In our study, the median time between symptom onset and the procedure was 9 h, which was shorter than that reported by Xian-Ming et al, suggesting that intestinal viability had been preserved.…”
Section: Discussioncontrasting
confidence: 59%
“…In our study, none of the 11 patients who underwent surgical reduction required resection due to bowel ischemia. Xian-Ming et al concluded that the median time between symptom onset and operative treatment for intussusception was longer in patients who lost intestinal viability (42 h) than for those who did not (19 h) [17]. In our study, the median time between symptom onset and the procedure was 9 h, which was shorter than that reported by Xian-Ming et al, suggesting that intestinal viability had been preserved.…”
Section: Discussioncontrasting
confidence: 59%
“…In that study, the median duration of symptoms in the overall patients, group with an unviable intestine, and group with a viable intestine was 23, 42, and 19 hours, respectively, and this result was significantly different. 14 Long duration of symptoms before presentation related to increase in the loss of intestinal viability. So, the duration of symptoms was not a contraindication for the nonoperative reduction, and some cases with a long symptom duration (minimum =1 hour and maximum =120 hours in success group) in our study had successful reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Intussusception is one of the most common causes of an acute abdomen in the pediatric emergency clinic and is the leading cause of acute bowel obstruction in infants and young children (1)(2)(3). In general, most intussusceptions can be categorized as primary or idiopathic, with thickened bowel wall lymphoid tissue (Peyer patches) acting as the lead point.…”
Section: Introductionmentioning
confidence: 99%